Satisfaction dan Repurchase Intention Pelanggan Kedai Bakso (Bagaimana Peran Perceived Quality?) - Safira Citra Fatina; Tezar Putra Nugraha; Nazar Muhammad Fadlullah; Muhammad Akmal Hatami; Usep Suhud (Fakultas Ekonomi Universitas Negeri Jakarta, 2020)
This study aims to examine the factors that influence the consumer's repurchase intention to visit a meatball shop. In this study, there are four variables used to measure repurchase intention, namely perceive quality, brand image, brand preference, and customer satisfaction. Data collection was carried out randomly from April to May 2020. Data was collected through a survey by distributing online questionnaires and selected using purposive sampling techniques. Total respondents in this study were 250 people consisting of 107 men and 143 women who had visited a meatball shop at least 3 times. Data were processed using exploratory factor analysis and structural equation models. The results of this study are perceived quality, brand image and customer satisfaction variables that have a positive and significant effect on repurchase intention. While brand preference variables do not have a significant effect on repurchase intention.